ANALISA SKALA PRIORITAS PROYEK PEMBANGUNAN JALAN DI KABUPATEN ACEH JAYA - Rahmad Fuadi; Muhammad Isya; Renni Anggraini (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
The limited funding of the Aceh Jaya regency government for development, including the construction of road infrastructure and the way in which road construction projects are still inaccurate and the process of budgeting unproportional work package by the Aceh Jaya regency government itself has not been able to fully meet the needs of road development in Aceh Jaya. Therefore, the need for priority scale that can be used as the basis of consideration in the process of development of road infrastructure development program. The purpose of this study is to determine the priority order of several road infrastructure development projects in Aceh Jaya regency by selecting or considering the appropriate criteria and according to development condition in Aceh Jaya regency using Multi Criteria Analysis (MCA) method. The weight of each criterion was calculated based on an assessment of the importance between the criteria obtained by interviewing stakeholders in Aceh Jaya regency government, while the alternative road performance score was obtained by analyzing and calculating the scale of the assessment quantitatively against each criterion based on secondary data obtained from related offices. Selected criteria are accessibility, environmental aspect, area development aspect, social aspect and development cost. Social aspect criteria get the highest weight of 0.279, it can be interpreted that social aspect is the main consideration in determining priority of road development in Aceh Jaya regency, because social aspect see influence of economic growth and social welfare of society from development of road infrastructure.  Based on the consideration of these criteria, the order of priority scale of road construction project in Aceh Jaya regency, where road in Calang city, Krueng Sabee sub-district is the first priority with score value 6,72.